Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08 2008
DOI: 10.1145/1544012.1544032
|View full text |Cite
|
Sign up to set email alerts
|

Towards high performance virtual routers on commodity hardware

Abstract: Modern commodity hardware architectures, with their multiple multi-core CPUs and high-speed system interconnects, exhibit tremendous power. In this paper, we study performance limitations when building both software routers and software virtual routers on such systems. We show that the fundamental performance bottleneck is currently the memory system, and that through careful mapping of tasks to CPU cores, we can achieve forwarding rates of 7 million minimum-sized packets per second on mid-range server-class s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 11 publications
(9 reference statements)
1
73
0
Order By: Relevance
“…Studies on data plane virtualization using Xen can also be found [2], where packet forwarding through guest domain is suggested in order to virtualize the data plane. Another work demonstrates how to make efficient use of multicore commodity hardware for virtual routers [3]. It also identifies performance bottlenecks associated with the currently available commodity hardware.…”
Section: Related Workmentioning
confidence: 99%
“…Studies on data plane virtualization using Xen can also be found [2], where packet forwarding through guest domain is suggested in order to virtualize the data plane. Another work demonstrates how to make efficient use of multicore commodity hardware for virtual routers [3]. It also identifies performance bottlenecks associated with the currently available commodity hardware.…”
Section: Related Workmentioning
confidence: 99%
“…The approach supports the load balancing between the cores inside the physical router and provides good performance in terms of throughput and latency. Egi et al [9] also proposed a design of a new platform for virtual routers on commodity hardware that is mainly driven by performance and flexibility for packet processing. The authors use Xen virtualization technology to host the guest domains for packet processing and forwarding in order to indentify the performance bottlenecks associated with the currently available commodity hardware.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The authors of Towards high performance virtual routers on commodity hardware [8] explored the limits of running a software router on a commodity server, and discovered that the memory subsystem is the source of bottlenecks in a typical mid-range multicore server system performing software routing. They were able to achieve forwarding rates of approximately 7-million packets per second for 40-byte packets, after carefully mapping routing processes to cores.…”
Section: Software Routingmentioning
confidence: 99%